Multiple cortical systems influence a single vibrissa muscle - Aman Maharjan; Jason M. Guest; Jean-Alban Rathelot; Fiorella M. Gomez Osorio; Peter L. Strick; Marcel Oberlaender (Proceedings of the National Academy of Sciences, 2025)
What is the neural substrate that enables the cerebral cortex to control a single mystacial vibrissa and orchestrate its movement? To answer this question, we injected rabies virus into the intrinsic muscle that protracts the rat C3 vibrissa and used retrograde transneuronal transport to identify the cortical neurons that influence the muscle. A surprisingly diverse set of cortical areas is the origin of disynaptic control over the motoneurons that influence the C3 protractor. More than two thirds of these layer 5 pyramidal neurons (L5PNs) are dispersed in frontal and parietal areas outside the primary motor cortex (vM1). This observation emphasizes the importance of descending motor commands from non-primary motor areas. More than a third of the L5PNs originate from somatosensory areas, such as the barrel field (vS1). The barrel field has been long considered a prototypic model system for studying sensory processing at the level of the cerebral cortex. Even so, we find that the number of L5PNs in vS1, and even their peak density, rivals the number and peak density of L5PNs in vM1. Thus, our results emphasize the importance of the barrel field in processing motor output. The distribution of L5PNs in vM1 and vS1 leads us to propose a model of vibrissa protraction in which vM1 output results in protraction, and vS1 output results in reciprocal inhibition (suppression) of protraction. This paired initiation and suppression of complementary movements may be a general feature of the descending output from the rodent M1 and S1.